High rate and stable cycling of lithium-sulfur batteries with carbon fiber cloth interlayer. (10th August 2016) - Yang, Yuxiang; Sun, Wang; Zhang, Jing; Yue, Xinyang; Wang, Zhenhua; Sun, Kening
Graphical abstract: A three-dimensional carbon fiber cloth (CFC) is placed between the separator and the sulfur cathode to accommodate and capture the soluble polysulfide intermediates. The cells with this interlayer show an initial discharge capacity of 6.89 mAh cm −2, which remains substantial after 100 cycles at 1C (6.69 mAh cm −2 ). Highlights: Carbon fiber cloth (CFC) is applied as interlayer between the separator and cathode. The interlayer helps to anchor the dissolved active material during cycling. A high-rate, long-life Li-S battery with high sulfur loading has been designed. Abstract: Significant efforts have been made to eliminate the shuttle effect created by the surface modification of separator or by adding interlayers. However, much of the research so far requires elaborate and costly material processing steps that did not necessarily result in substantially improved cell performances. In this contribution, a three-dimensional carbon fiber cloth (CFC) is placed between the separator and the sulfur cathode to accommodate and capture the soluble polysulfide intermediates. The cells with this interlayer show an initial discharge capacity of 6.89 mAh cm −2, which remains substantial after 100 cycles at 1C (6.69 mAh cm −2 ). CFC interlayers provide an efficient and cost effective route for developing promising lithium-sulfur batteries with long cycle stability and good rate capability.